PENGARUH PERMAINAN LEGO TERHADAP KREATIVITAS ANAK KELOMPOK B USIA 5 – 6 TAHUN DI TK GEMBIRA JATIBENING BEKASI JAWA BARAT - Siti Astuti; Delina Kasih (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2021)
Lego games are a kind of jigsaw game tool made of small plastic that can be arranged into models of cars, trains, buildings, cities, statues, airplanes, spaceships and robots and are famous in the world, especially among children. This study aims to determine how much influence the Lego game has on the creativity of group B children aged 5-6 years at Gembira Kindergarten Jatibening Bekasi. The research method used is a quantitative method and the method used in this study is a correlational method with a survey procedure with a questionnaire instrument. The study population was group B children at Gembira Jatibening Kindergarten Bekasi with a sample of 13 children. The conclusion of the research shows that the Cronbach alpha coefficient for the Lego game instrument is 0.737 and the children's creativity questionnaire is 0.810, so both instruments are declared reliable. The results of this study have implications as input for other teachers in order to improve themselves in relation to the teaching that will be achieved by students, thus providing the right learning method.